PROBLEMS AND PROSPECTS OF UNIVERSITY-INDUSTRY INTERACTION - Bredikhin, Vladimir Viktorovich (Journal of Applied Engineering Science, 2019)
The main goal of the presented research paper is to find solutions to existing problems in the field of interaction between the university and the industrial sector. This goal is achieved by solving the following tasks: 1) analyze of the evolution of university-industry interaction; 2) analyze of the situation in the field of university and business / industry interaction; 3) focusing on the need for universities - industry cooperation and identifying key barriers in their interaction; 4) consideration of formats for university and business / industry interaction. The objectives of this article are achieved through a review of the existing literature, a synthesis of the necessary knowledge about the interaction of the university and the industrial sector, the analysis of the need for interaction, key barriers, and interaction formats to formulate proposals that improve cooperation and identify the most effective ways of partnership. This analysis covers the following documents: information and analytical sources, research projects of predecessors, data from international research organizations, and historical documents.